If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -2x = 12 + 4x Solving 18 + -2x = 12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 18 + -2x + -4x = 12 + 4x + -4x Combine like terms: -2x + -4x = -6x 18 + -6x = 12 + 4x + -4x Combine like terms: 4x + -4x = 0 18 + -6x = 12 + 0 18 + -6x = 12 Add '-18' to each side of the equation. 18 + -18 + -6x = 12 + -18 Combine like terms: 18 + -18 = 0 0 + -6x = 12 + -18 -6x = 12 + -18 Combine like terms: 12 + -18 = -6 -6x = -6 Divide each side by '-6'. x = 1 Simplifying x = 1
| (3x+4y)(3x+4y)= | | c-19=13 | | 14.7xp=390 | | 2z+32=56 | | 34x+25=25+-20x | | -5+w=12 | | e+18=45 | | xyz=20 | | 51=-9x-6 | | -3(n-8)=28-7n | | Y=(30-2x)(40-2x)(x) | | 4x-6x+12=20 | | 1307.2=17.2a | | 5-3x=19+4x | | 30-5v+2v=3v-12 | | 4n-12=11-4n | | 15x+8y=131 | | -131=-3-4(8-3v) | | a-20=17 | | -3m+4=-2m-5 | | 12=10y-8y | | x-7=3(x-4) | | 6-x=3(x+10) | | 10b+8b=360 | | 3075=37.5a | | 6x^2+36x+192=0 | | 5x-12=9x+5 | | 3(x+2)+1=2x-8+x+13 | | -16=2a-6a | | 637=13a | | x^2=-2+15 | | 5z=1.7+4.3 |